Mind Your State for Your State of Mind. - HELLAND, PAT (Communications of the ACM, 2018)
The article discusses changes to the interactions between data storage and computer applications. Topics include improvements to microservice-based applications, changes to durable state semantics, and transactions related to record writes. The significance of nonlinear history is addressed in relation to data transactions.